Children’s Drawing and Graphic Development: An Empirical Study of the Developmental Stages According to Lowenfeld - Paula Gil-Ruiz; Victoria Martinez-Verez; William Ospina Toro; Walter Castañeda Marulanda (Education Sciences)
Children’s graphic development reflects cognitive, emotional, motor and social processes, and is an indicator of the infant’s integral development. This study analyzed the validity of Viktor Lowenfeld’s developmental model in children aged 3 to 5 years, assessing whether the stages proposed by the author correspond to the patterns of graphic representation currently observed. A mixed design with a descriptive–comparative approach was used. The sample consisted of 218 drawings collected in educational centers in Madrid. Each drawing was evaluated according to criteria derived from Lowenfeld’s model (stroke, motor control, symbolism, use of color, spatial organization) and classified into one of the five developmental stages. The analysis included descriptive statistics, chi-squared tests (χ2 = 104.92, gl = 10, p < 0.0001), and Spearman correlations (ρ = 0.661, p < 0.0001), in addition to qualitative interpretation by inter-rater consensus. The results confirm that the general graphic sequence follows Lowenfeld’s scheme, but with notable variations in the age of onset of each stage. Pre-schematic manifestations were observed in children as young as 3 years old and persistence of scribbling in some 5-year-olds. These findings point to the influence of individual, sociocultural, and technological factors on the rate of graphic development. Lowenfeld’s model remains a valid framework for observing children’s drawing, but its application should be flexible. Interindividual differences and contemporary visual culture require a pedagogical adaptation that addresses the diversity of developmental rhythms. Its integration with inclusive methodologies and future cross-cultural studies is suggested.